Kuwait : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper on Kuwait reviews its economic development strategy and uses a variety of analytical methods to highlight Kuwait's policy challenges and their effectiveness. Kuwait has accumulated large fiscal surpluses, enabling it to build up a sizable asset position for future generations. The fiscal position is also expected to remain comfortable over the medium term, but the recent rapid increase in expenditures raises doubts about the sustainability of the current fiscal stance over the longer term.